Regulação da expressão da proteína cinase PKR na ausência de interferons(IFNs) e seu papel na resposta celular mediada por agonistas dos receptoresTLR2 e TLR4 - Paula Cristiane Motta Sales (2012)
The role of protein kinase R (PKR) in the antiviral cell state induced byinterferons (IFNs) is well known. The increase in its expression in response to stimulation by IFNs results in its autophosphorylation and phosphorylation of its substrate eIF2-alpha. This molecular event interferes with translation initiation of mRNA, which in turn results in inhibition of protein synthesis. Recent studies suggest the involvement of PKR in bacterial infections. However, how PKR is activated and what is its biological role in these infections is still largely unexplored. Thus, the central objective of our study was to examine the regulation of expression of PKR in the signaling pathway triggered by agonists of TLR2 andTLR4 in a human promonocytic, THP-1. THP-1 monocytes were treated with LPS (TLR4 agonist) or Pam3CSK4 (TLR2 agonist) in increasing doses or at different time intervals. At the end of these treatments, total RNA and protein extracts were obtained for analysis of the relative abundance of mRNA PKR by real time PCR and protein levels by western blot assays, respectively. The results showed a significant increase in the levels of mRNA PKR and PKR protein. Surprisingly, we did not observe any increase in the levels of transcripts of IFN-beta or subtypes of IFN-alpha. Moreover, treatment of THP-1 cells with LPS or Pam3CSK4 did not result in STAT1 phosphorylation. Supernatants taken from THP-1 cells treated with LPS or Pam3CSK4 did not caused the activation of PKR or ISG56 promoters in reporter gene assays carried out in HEK293T cells. These results provide evidence that in THP-1 monocytes exposed to stimulation with TLR4 and TLR2 agonists, neither transcriptional activation nor production of type I IFNs is observed, and therefore the PKR expression occurs in the absence of IFNs. Once the promoter region of PKR contains other regulatory elements as candidates for its expression regulation, including NF-IL6, NF-kB, Sp1 and Sp3, we decided to assess the effect of three pharmacological inhibitors. The pretreatment of theTHP-1 cells with TPCK or Bay11 7082, pharmacological inhibitors of thetranscription factor NF-B, inhibited the PKR expression induced by bacterial agonists. The same was observed when cells were pretreated with Mithramycin, an inhibitor of Sp1/Sp3 transcription factor. However, analysis of the phosphorylation of STAT1 in THP-1 cells differentiated to macrophages suggests the involvement of IFNs in cells treated with the TLR4 agonist, but not with TLR2. The monocytes are one of the major cells of the innate immune responses and are essential for host defense against a wide range of pathogens, having an important role in sepsis. We analyzed and compared the survival of WT and PKR-/-polymicrobial sepsis model. The results indicated that PKR appears to play a detrimental role to the host, as PKR-deficient mice survive from sepsis. Our results demonstrate that PKR expression in human monocytes stimulated with bacterial agonists TLRs occurs independently of IFNs, and that the regulatory mechanisms of its expression involve transcription factors that are critical in the inflammatory response. Furthermore, results obtained from the experiments in vivo demonstrate that PKR is an important target for studies of sepsis. Therefore, our study providesnew insight into the mechanisms of transcriptional activation of PKR and its role on the innate immune response against bacterial pathogens.